Effects of acupuncture on the anxiety-like behavior induced by withdrawal from chronic morphine use. (18th January 2018) - Kim, Dong Hyeon; Kim, Nam Jun; Zhao, Rong Jie; Kim, Da Hye; Yang, Chae Ha; Kim, Hee Young; Gwak, Young S.; Jang, Eun Young; Kim, Jae Soo; Lee, Yun Kyu; Lee, Hyun Jong; Lim, Sung Chul; et al.
Highlights: Open arms time in the elevated plus maze was reduced by withdrawal from chronic morphine use. Acupuncture at the specific acupoint HT7, but not at control acupoint LI5, increased open arms time. Effects of Acupuncture were blocked by GABAA receptor antagonist. Acupuncture inhibits the anxiety-like behavior induced by withdrawal from chronic morphine, at least in part, via GABAA receptor pathway. Abstract: Objectives: In the previous studies, it has been demonstrated that acupuncture treatment was effective on the suppression of withdrawal signs as well as self-administration behavior induced by morphine. Based on, the present study has investigated whether acupuncture could attenuate the anxiety-like behavior induced by withdrawal from chronic morphine treatment. Materials & methods: Male Sprague-Dawley rats weighing 270–300 g were treated saline or morphine hydrochloride (10 mg/kg, s.c.) for 2 weeks. Following abstinence of 5 days in home cage, rats were subjected to the measurement of anxiety-like behavior in the elevated plus maze. Bicuculline (1 mg/kg, i.p.) and SCH 50911 (2 mg/kg, i.p.) were used to investigate the possible mechanism of acupuncture effects focusing on the GABA receptors system. Results: Acupuncture at HT7 increased the time spent in open arms significantly. Also, these effects of acupuncture at HT7 were blocked by GABAA receptor antagonist. Conclusion: Results of the present study suggest that acupuncture at HT7 can attenuate anxiety-like behavior induced by withdrawal from chronic morphine treatment through the mediation of GABAA receptor system.